Efectos de los ejercicios aeróbicos en el mantenimiento de la salud del adulto diabético - Erika Elizabeth, Vacacela Tacuri (2019)
: This research focuses on adult patients suffering from diabetes, and what are the effects of aerobic exercises on health maintenance. Within the world population, 1-2% of people suffer from diabetes being a global problem in the field of health, this has increased from 108 million in 1980 to 422 million in 2014, which has a prevalence in adults ( over 18 years old) has increased from 4.7% in 1980 to 8.5% in 2014, in which the least developed countries have been the most affected. For this reason we have seen the need to analyze the relationship of aerobic exercise with diabetes and whether they have a positive or negative effect. Since Diabetes is a problem worldwide, it is very important to inform about the benefits of exercise, in its prevention, care and maintenance. The research is based on a collection of scientific articles, which refer to the effects of exercises on diabetics and as an aid in their health maintenance, the methodology includes the logical process and analytical thinking; the inductive method that has been used based on the analysis and correlation of aerobic exercises and the benefits such as glycemic control in adult diabetics which allowed us to start from a premise and reach a conclusion, the approach was bibliographic as it was analyzed different types of documents especially scientific articles. With a collection of 35 articles which demonstrated that aerobic exercise has multiple benefits in the maintenance of the diabetic adult.